Association between 2d:4d ratio prevalence and females involved in motorvehicle accident - Abdullah, Muhammad Azhar (2015)

(untitled)
Introduction: Digit ratio (2D:4D) is a putative marker of prenatal hormone exposure. A lower digit ratio has been suggested as an index of higher testosterone relative to estrogen exposure during prenatal development. Digit ratio has been associated with a variety of psychological sex-dimorphic variables, including spatial orientation, aggression, or risk-taking behaviour. Objectives: The present study aimed to look for any correlation between female involved in motorvehicle accident (MVA) and digit ratio. Digit ratio was assessed via hand radiographs. Patients and Methods: Each hand was classified into three types according to the relative length of the index and ring finger: Type 1 (index longer than ring) common female pattern, Type 2 (index = ring) intermediate pattern and Type 3 (index shorter than ring) common male pattern. For both index and ring fingers we measured from base of proximalphalanx to tip of distal phalanx. Two group of patient was identified one which involved in (MVA) and another group not involved in (MVA) and the association between this 2 group and digit ratio was studied. Result: The result showed that female which involved in MVA most of them having type 3 digit ratio which is male pattern 53.6% while those not involved in MVA are type 1 digit ratio which is female pattern 38.1%. Conclusion: Therefore, the result of this study creates a new awareness as to the potential female with low digit ratio (type 3) which is male pattern associated with MVA and this also provide some support for the digit ratio as potential predictor of accident proneness.